A5.12 Atherosclerosis severity is independent of endogenous IL-33 signalling. (13th February 2015) - Martin, P; Palmer, G; Rodriguez, E; Woldt, E; Mean, I; Talabot-Ayer, D; James, RW; Smith, D; Kwak, BR; Gabay, C
Abstract : Background and objectives: Interleukin (IL)-33 is a cytokine of the IL-1 family, which signals through the ST2 receptor. Previous work demonstrated that the systemic administration of IL-33 reduces the development of atherosclerosis in the apolipoprotein E-deficient (ApoE -/- ) mouse model of the disease by induction of a Th1-to-Th2 shift. However, the role of endogenous IL-33 in the atherogenesis remains elusive. Materials and methods: Atherosclerosis was induced in 10 week-old ApoE -/-, IL-33 -/- ApoE -/- and ST2 -/- ApoE -/- mice by feeding a high-cholesterol diet (1.25%, no cholate) for 10 weeks. Additionally, a group of ApoE -/- mice were injected with a neutralising anti-ST2 antibody or an isotype control during the period of the diet. The atherosclerotic lesion development was measured with Oil Red O in the thoracic-abdominal aorta and in the aortic sinus. The mRNA levels of several cytokines, including IL-6, IFNγ, IL-17, IL-5 and IL-10 were assessed in the aorta and in in vitro -stimulated lymph node cells. Results: We observed no differences in lipid-staining area in the aortas of IL-33 -/- ApoE -/- mice (8.84 ± 0.97; mean ± SEM; n = 9–25), ST2 -/- ApoE -/- mice (6.95 ± 0.78), ApoE -/- mice untreated (7.05 ± 0.78), ApoE -/- mice injected with either the neutralising anti-ST2 antibody (6.08 ± 0.79) or the isotype control (6.16 ± 0.86) after high-cholesterol diet feeding. Similar results were obtained in the aortic sinus compared to ApoE -/- controls. Total serum cholesterol and triglyceride levels were not different compared to ApoE -/- controls. IL-33 expression in aortic tissue was comparable in ApoE -/- and ST2 -/- ApoE -/- mice and absent in IL-33 -/- ApoE -/- mice. There was no difference in the transcript levels of inflammatory cytokines in the aorta and in in vitro -stimulated lymph node cells. Conclusions: These data indicate that in contrast to the anti-atherosclerotic effect of systemically administered recombinant IL-33, the endogenously produced cytokine and its receptor do not significantly influence the severity of atherosclerosis in ApoE-deficient mice fed with a high-cholesterol diet.